Full Stokes ice-flow modeling of the high-Alpine glacier saddle Colle Gnifetti, Monte Rosa: Flow field characterization for an improved interpretation of the ice-core records - Licciulli, Carlo (Universität Heidelberg, 2018)
The high-Alpine glacier saddle Colle Gnifetti (CG), Monte Rosa massif, is the only cold glacier archive in the European Alps oering detailed ice-core records on the millennial-scale. However, the highly irregular snow deposition pattern and the complex ow regime produce depositional noise and upstream eects, which hinder the full interpretation of the ice-core records in terms of past atmospheric changes. In this context, this work focuses on establishing a three-dimensional full Stokes ice- ow model of the CG saddle, with the main objective to calculate precise backward trajectories of existing ice-core sites, which is necessary to evaluate potential upstream eects. The developed full Stokes model is fully thermo-mechanically coupled and includes rn rheology, rn densication and enthalpy transport, with consideration of atmospheric temperature changes of the last century, strain heating and surface meltwater refreezing. The simulations are performed using the state-of-the-art Finite Element software Elmer/Ice. The CG full Stokes model is validated by comparison with measurements of surface velocities, accumulation, annual layer thickness, borehole inclination angles, density and temperature. Estimated using dierent bedrock topographies, the error of the calculated source point positions on the glacier surface amounts to 10% of the distance to the corresponding drill site. Moreover, the three-dimensional age eld of the glacier is calculated with an uncertainty of 20%. The calculated chronologies of four out of ve ice cores are consistent with experimental dating results, based among others on layer counting and 14C measurements.